The Frequency of V122I Transthyretin Mutation in a Cohort of African American Individuals With Bilateral Carpal Tunnel Syndrome - Shije, Jeffrey Z.; Bautista, Maria A. B.; Smotherman, Carmen (Frontiers in Neurology, 2022)
Introduction: Hereditary transthyretin amyloidosis (hATTR) can cause multisystem organ disorders including polyneuropathy and cardiomyopathy. Amongst the many known pathologic mutations of the transthyretin (TTR) gene, the Val122Ile (V122I) mutation can be found in 3-4% of African Americans. Up to 47% of patients with the V122I hATTR cardiomyopathy had a history of carpal tunnel syndrome (CTS). This raises the question should we screen for this mutation in African Americans with bilateral CTS for the purpose of preventing advanced disease associated with hATTR. This is a prospective pilot study to determine the likelihood of African Americans with bilateral CTS having the V122I mutation and whether various clinical factors contribute to that probability. Methodology: Adult African American patients without prior history of amyloidosis diagnosed with bilateral CTS were recruited for the study. They received genetic testing to screen for a TTR mutation. They also completed questionnaires to screen for symptoms of cardiomyopathy and neuropathy, other risk factors for CTS, and family history of CTS and cardiomyopathy. Result: Two of the sixteen patients (12.5%) in this cohort were found to have the V122I mutation. The absence of polyneuropathy and cardiomyopathy symptoms, presence of other CTS risk factors, and absence of family history of CTS and cardiomyopathy did not decrease the likelihood of V122I mutation in this cohort. Conclusion: The frequency of V122I transthyretin mutation in African Americans with bilateral CTS may be higher than 3-4%. The presence of bilateral CTS alone may be a justification to screen for TTR mutation in this population.